Cross-Border Trade Efficiency: The Impact of Indonesia–Thailand QRIS on the ASEAN Economy - Atika Sofia; Fahira Aulia; Intan Purwati; Marsalina Putri; Nur Hasna Sya’baniyah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Nowadays, digitalization of payment systems has become an important pillar in accelerating economic integration in Southeast Asia. This study analyzes the efficiency of cross-border trade through the QRIS cooperation between Indonesia and Thailand, which has been integrated since 2022. Using the framework of Institutional Liberalism, this study examines how regional payment connectivity can reduce transaction costs and improve exchange rate transparency. The findings show that the collaboration between QRIS and PromptPay supports the use of local currencies through Local Currency Settlement, thereby reducing dependence on the US Dollar and international payment networks such as Visa and Mastercard. This integration has a positive impact on tourism and MSMEs by helping small business actors reach foreign consumers more practically and efficiently. Although challenges remain in financial literacy and digital infrastructure readiness, this model can serve as a blueprint for ASEAN’s digital economic sovereignty.